The Relevance of Food Constituents to the Irritable Bowel Syndrome: A Rome IV-Based Prevalence Study Among Medical Students - Ahmed H. Mujamammi; Rasha Al-Hamdan; Essa M. Sabi; Zyad A. Aldosari; Abdullah M. Shadid; Abdulrahman Shadid; Salman Alagla; Hameed S. Humaid; Talal Abozaid; Nahla Azzam (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Irritable bowel syndrome is prevalent in the general population. This study investigates the association between dietary intake and irritable bowel syndrome in medical college students at King Saud University besides its prevalence. Materials and Methods: This is an analytical cross-sectional study of 426 students (271 males and 155 females, age 21.21 ± 1.58 years) from 5 academic levels of King Saud University Medical College. A self-reported questionnaire for Rome IV criteria was completed by each participant. They also filled out a food frequency questionnaire to assess their nutritional intake. Results: The overall prevalence of irritable bowel syndrome was 17.8% without correlation to age and academic year in Medical School. However, the prevalence was higher in females than in males (40/115 vs. 36/235, P = .001). The irritable bowel syndrome group consumed significantly more energy, carbohydrates, and saturated fatty acids, while the non-irritable bowel syndrome group consumed significantly more fibers and niacin (P < .001 and P = .005, respectively). Conclusion: About 17.8% of medical students had irritable bowel syndrome with a greater prevalence in females. The irritable bowel syndrome group consumed significantly more energy, carbohydrates, and saturated fatty acids, while the non-irritable bowel syndrome group consumed significantly more fibers and niacin. Our results did not show any significant association between irritable bowel syndrome and fermentable oligosaccharide, disaccharide, monosaccharide, and polyol intake. Overall, both groups were not adhering to the Saudi dietary recommended intake. Cite this article as: Mujamammi AH, Al-Hamdan R, Sabi EM, et al. The relevance of food constituents to the irritable bowel syndrome: A Rome IV-based prevalence study among medical students. Turk J Gastroenterol. 2023;34(8):859-865.